Myocardial infarction with nonobstructive coronary arteries: current state of the problem and diagnostic approaches - A. S. Shilova; A. V. Sherashov; E. S. Pershina; D. Yu. Shekochikhin; M. Yu. Gilyarov (Klinicist, 2019)
The importance of the problem of myocardial infarction (MI) with nonobstructive coronary arteries (MINOCA) increases yearly with accumulation of more statistical data. According to current knowledge, MINOCA on average comprises 6 % of all MI cases. According to the Fourth Universal Definition of MI and the consensus document of the MINOCA task team, MINOCA diagnosis can be made for combination of MI criteria with insignificant coronary artery disease established using coronary angiography and absence of another significant cause of elevated troponin level. As it is known, elevated troponin level in blood test can be caused by various pathological states of the cardiac and extra-cardiac nature. Therefore, every suspected MINOCA case must be confirmed. Among MINOCA diagnostic methods, apart from electrocardiography, echocardiography and coronary angiography necessary for MI verification, the most important are magnetic resonance imaging with intravenous Gadolinium contrast which allows to differentiate ischemic heart disease from other myocardial disorders of varied genesis. Additionally, the causes of every case of MINOCA can be determined using intravascular visualization methods (optical coherence tomography, intravascular ultrasound imaging). Considering vasospasm is one of the mechanisms of myocardial ischemia underlying MINOCA, pharmacological tests with acetylcholine, ergonovine can be of certain interest. Thrombophilia plays a significant role in MI and MINOCA genesis. Analysis of polymorphisms of genes participating in expression of blood coagulation proteins is of special importance. The necessity of determination of the causes of every MINOCA clinical case is based on the requirement for adequate therapy different for every pathological type.